"Biochar in combination with compost reduced Pb uptake and enhanced the growth of maize in lead (Pb)‑contaminated soil exposed to drought stress " (2010)
Crops are constantly faced with the challenges of different abiotic stresses on the field. Development of sustainable approach for stress amelioration on crop is pertinent. This study investigated the ameliorative roles of biochar and compost on maize crop simultaneously subjected to drought and heavy metal (Pb) stresses. Metal stress was imposed by growing maize on Pb-contaminated soil while drought stress was imposed by reducing the soil field capacity to 25 and 50%. Four levels (0, 5, 10 and 15 t/ha) of biochar and compost replicated three times as well as their combinations were used. Pb uptake, translocation factors, photosynthetic pigments, osmolytes (proline and cysteine), biomass accumulation in stressed maize crop, and post-cropping soil Pb concentration were determined. Combination of stresses reduced biomass accumulation in maize. Biochar in combination with compost, however, enhanced biomass production in stressed maize crop by 50–75% compared to unamended soil (control). Proline accumulation was more under the single stress of heavy metal (100% FC) compared to combined stresses. Unlike proline, combined stresses of Pb and 50% FC enhanced chlorophyll and cysteine accumulation more than single stress. Their concentrations were further increased with amendments compared to control. Pb accumulation in maize crop was more under combined stresses than single stress (100% FC). Compared to other soil amendments, application of biochar alone at 10 t/ha, generally reduced Pb uptake by maize and post-cropping soil Pb concentration. Biochar and compost reduced Pb uptake, and enhanced biomass and osmolyte production in stressed maize crop.